Measurement of Bioactivity of Immunomodulatory Treatment of Relapsing Multiple Sclerosis. With Emphasis on MxA Protein - Vallittu, Anna-Maija (fi=Turun yliopisto|en=University of Turku|, 2007)
Background Multiple sclerosis (MS) is a demyelinating disease of the central nervous system, which mainly affects young adults. In Finland, approximately 2500 out of 6000 MS patients have relapsing MS and are treated with disease modifying drugs (DMD): interferon- β (INF-β-1a or INF-β-1b) and glatiramer acetate (GA). Depending on the used IFN-β preparation, 2 % to 40 % of patients develop neutralizing antibodies (NAbs), which abolish the biological effects of IFN-β, leading to reduced clinical and MRI detected efficacy. According to the Finnish Current Care Guidelines and European Federation of Neurological Societis (EFNS) guidelines, it is suggested tomeasure the presence of NAbs during the first 24 months of IFN-β therapy. Aims The aim of this thesis was to measure the bioactivity of IFN-β therapy by focusing on the induction of MxA protein (myxovirus resistance protein A) and its correlation to neutralizing antibodies (NAb). A new MxA EIA assay was set up to offer an easier and rapid method for MxA protein detection in clinical practice. In addition, the tolerability and safety of GA were evaluated in patients who haddiscontinued IFN-β therapy due to side effects and lack of efficacy. Results NAbs developed towards the end of 12 months of treatment, and binding antibodies were detectable before or parallel with them. The titer of NAb correlated negatively with the amount of MxA protein and the mean values of preinjection MxA levels never returned to true baseline in NAb negative patients, but tended to drop in the NAb positive group. The test results between MxA EIA and flow cytometric analysis showed significant correlation. GA reduced the relapse rate and was a safe and well-tolerated therapy in IFN-β-intolerant MS patients. Conclusions NAbs inhibit the induction of MxA protein, which can be used as a surrogate marker of the bioactivity of IFN-β therapy. Compared to flow cytometricanalysis and NAb assay, MxA-EIA seemed to be a sensitive and more practical method in clinical use to measure the actual bioactivity of IFN-β treatment, which is of value also from a cost-effective perspective.

Taustaa Multippeliskleroosi (MS) on nuorten aikuisten merkittävin demyelinoiva keskushermoston sairaus. Suomessa on 6000 MS potilasta, joista noin 2500 saa aaltomaisesti etenevään MS-tautiin taudinkulkua muuntavaa lääkehoitoa: beetainterferonia (INF-β-1a tai INF-β-1b) tai glatirameeriasetaattia (GA). Käytetystä IFN-β- valmisteesta riippuen 2-40 %:lle hoidetuista potilaista kehittyy IFN neutraloivia vastaaineita (NAb), joiden on todettu vähentävän hoidon tehoa sekä kliinisen oirekuvan että aivojen magneettitutkimuksessa todettujen muutosten perusteella. Suomalaisen Käypä Hoito ja eurooppalaisen EFNS suosituksen mukaisesti NAb tulisi mitata ensimmäisten 24 kk aikana IFN-β-hoidon aloituksesta. Tarkoitus Tämän väitöskirjatyön tarkoituksena oli mitata IFN-β-hoidon biologista vastetta mittaamalla IFN indusoimaa MxA proteiinia (myxovirus resistance protein A) ja arvioida sen korrelaatiota neutraloiviin vasta-aineisiin. Lisäksi kehitettiin aiempaa nopeampi ja yksinkertaisempi MxA proteiinia mittaava EIA-testi ja selvitettiin glatirameeriasetaatin siedettävyyttä ja turvallisuutta MS-potilailla, jotka olivat joutuneet keskeyttämään IFN-β-hoidon sivuvaikutusten ja tehon heikkenemisen vuoksi. Tulokset NAbs kehittyivät ensimmäisten 12 hoitokuukauden aikana ja sitoutuvat vasta-aineet ilmaantuivat joko edeltävästi tai samanaikaisesti NAb kanssa. NAb tiitterien ja MxA proteiinitason välillä oli negatiivinen korrelaatio. MxA proteiinin perustaso laski NAb positiivisilla, mutta ei NAb negatiivisilla potilailla. MxA-EIA testin ja virtaussytometrianalyysin tulosten välillä oli merkitsevä korrelaatio. GA vähensi relapsien määrää ja osoittautui turvalliseksi ja hyvin siedetyksi hoidoksi potilailla, jotka eivät kyenneet käyttämään IFN-β-hoitoa. Johtopäätökset NAb estävät MxA proteiini-induktiota, jota voidaan käyttää IFN-β- hoidon biologisen vasteen mittarina. Virtausytometrianalyysiin ja NAb testiin verrattuna MxA-EIA proteiinimääritys on helppokäyttöisempi ja kliiniseen käyttöön kustannus-vaikuttavuudellista merkitystä. neutraloivat vasta-aineet, sitoutuvat vasta-aineet, immunogeenisyys, MxA riittävän herkkä menetelmä mittaamaan IFN-β-hoidon biologista vastetta. Tällä on myös kustannus-vaikuttavuudellista merkitystä.
Keywords: Adult; Treatment Outcome; GTP-Binding Proteins; Multiple Sclerosis; Interferon-Beta; Female; Male; Adjuvants, Immunologic - administration & dosage; Middle Aged; Antibodies - blood; Gene Expression; Peptides